Surgical treatment of the knee joint contractures after total knee arthoplasty - Alexander A. Akhpashev; Leonid K. Brizhan; Aleksander A. Artemiev; Mikhail A. Bolotnikov; Aleksander A. Shipulin; Ali M. Kashoob (Клиническая практика, 2020)
Background. The development of contractures after total knee replacement is most often associated with arthrofibrosis and constitutes up to 1.35.7% of the total number of cases of joint replacement. The conservative treatment is ineffective. Arthrolysis is pathogenetically substantiated (arthroscopic or open).